INNOVATIVE APPROACHES AND PROSPECTS FOR THE DEVELOPMENT OF SETTLEMENT AND CASH SERVICES FOR BANKING CLIENTS - NIKOLCHUK, Yuliia; KRUT, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes transformation processes in the field of settlement and cash services (SCS) of bank clients in the context of active digitalization of the financial sector of Ukraine. The importance of SCS as one of the basic functions of banking activities, which ensures reliable, fast and convenient financial transactions for individuals and legal entities, is substantiated. Under the influence of innovative technologies, settlement and cash services are undergoing significant changes: processes are being automated, security is being increased, and the functionality of services is being expanded.The article describes modern digital tools that are being actively implemented by banks, in particular JSC Oschadbank. The functionality of such platforms as Oschad 24/7, CorpLight, chatbots with artificial intelligence elements, mobile branches, the Power Banking system and online services that provide customer service even in crisis or emergency conditions is covered in detail. The bank's strategic directions for the modernization of RKO are revealed, focused on increasing the accessibility, speed, reliability and personalization of banking services.The regulatory and institutional support for digital transformation in the banking sector of Ukraine is analyzed, in particular the initiatives of the National Bank of Ukraine and the Ministry of Digital Transformation. The focus is on the integration of banking services with state electronic platforms (for example, "Diya"), as well as the impact of digital tools on reducing operating costs, optimizing business processes and increasing the competitiveness of banking institutions.As a result of the study, the main directions of promising development of RKO are formulated: expanding the functionality of mobile banking, developing contactless and biometric technologies, deeper integration of AI and data analytics, as well as increasing the digital literacy of clients. It is concluded that innovative approaches to RKO are a key factor in the effective adaptation of banks to new challenges in the economic and social environment.
Keywords: settlement and cash services; digitalization; Internet banking; remote service; artificial intelligence; fintech; Power Banking; CorpLight; Savings 24/7; digital transformation